Extended Composite Right/Left-Handed Transmission Line and Dual-Band Reactance Transformation - Yuming Zhang; Barry Spielman (Journal of Electrical and Computer Engineering)
An extended composite right/left-handed transmission line is introduced, and its dual-band bandpass filter characteristics are explored. Novel reactance transformations, derived from this transmission line, are formulated to transform a low-pass prototype filter into a dual-band bandpass filter with arbitrary dual pass bands, well-defined in-band attenuation ripples, and high out-of-band rejection. The physical insight into such a dual-band bandpass filter is provided with a dispersion analysis. The transformations are verified by simulated results for dual-band bandpass filters.